IMPLEMENTATION OF GUIDANCE AND COUNSELING TECHNIQUES AT AL KAUTSAR KINDERGARTEN IN SAMARINDA CITY - Salsabila Rizky al Fahmi; Ayu Aprilia Pangestu Putri; Lailatul Badriyah; Nur Rafizah; Tiara Septia Utami (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the implementation of guidance and counseling techniques at TK Al Kautsar in Samarinda City. The research applied a descriptive qualitative approach using a case study method. Data were collected through direct observation in the school environment, in-depth interviews with classroom teachers and the school principal, as well as documentation of various activities related to the implementation of guidance and counseling services. The results reveal that the techniques used in the guidance and counseling program at TK Al Kautsar include repeated explanations, the use of short and clear instructions, and personalized approaches tailored to the needs, interests, and characteristics of each child. These strategies have proven effective in enhancing children's understanding of both social and academic content. Furthermore, they positively influence emotional development, such as improving self-confidence, emotional regulation, and peer interaction skills. Overall, the implementation of guidance and counseling techniques at TK Al Kautsar has been effective in supporting early childhood growth and development. However, the study highlights the need for continuous professional development for teachers, particularly in the area of child-centered counseling techniques. It is also recommended that schools build stronger collaboration with parents to create a supportive and holistic environment for the children’s learning and development. By optimizing these elements, the guidance and counseling program can play a more strategic role in nurturing children's social-emotional skills, preparing them for future learning experiences, and supporting their overall well-being in early education settings.